Legal responses to HIV and AIDS - Chalmers, James, LLB. (Oxford ; Portland, Oregon : Hart Publishing, 2008)
This book examines legal responses to HIV and AIDS and evaluates these issues in comparative perspective. It draws on legal responses to other sexually transmitted infections and contagious diseases.
Introduction and overview -- Testing for HIV : legal and ethical problems -- Confidentiality and duties to warn -- Harm minimisation and the law -- HIV and deportation from the United Kingdom -- The criminalisation of HIV transmission -- Access to treatment : a brief note on patent law.
Includes bibliographical references and index.
Keywords: HIV infections -- Law and legislation -- Great Britain; AIDS (Disease) -- Law and legislation -- Great Britain; HIV-positive persons -- Legal status, laws, etc. -- Great Britain; AIDS (Disease) -- Patients -- Legal status, laws, etc. -- Great Britain; HIV Infections -- Great Britain; Public Health -- legislation & jurisprudence -- Great Britain; Health Policy -- legislation & jurisprudence -- Great Britain; Health Services Accessibility -- legislation & jurisprudence -- Great Britain; Patient Rights -- legislation & jurisprudence -- Great Britain